Knowledge Management and effective leadership Is the Only Solution for Sustainable Growth (Performance) of India’s Corporate Sector: A Mediation Role of Knowledge Centered Culture - et al., Lekhaz Atyam (International Journal of Advanced Science and Technology, 2019)
Knowledge is a power a well-known proverb. Recently, in the era of globalization world economies are transforming into knowledge-based economies for long term sustainable growth. The current study aims to measure the impact of knowledge management and effective leadership on organizational performance with mediating role of knowledge infrastructure capability in corporate sector in India. The service, telecommunication, IT, and manufacturing industries are included in this study for targeting the respondents. Data was collected through self-administer questionnaire by using simple random sampling from a sample of 144 employees of organizations. Further, data is analyzed by using structural modeling equation method PLS. Results, of the study shows that knowledge management and effective leadership has significant positive impact on organizational performance and knowledge centered culture (KCC) fully mediate the relation.